A Case Study: The Underrepresentation of African American Female Principals and Superintendents in a Small Rural School District in the South - Hatcher, Heroyline D. (My University, 2025)
K-12 public school systems in the U.S. show a notable underrepresentation of female educators in top leadership roles, such as principals and superintendents (National Center for Education Statistics [NCES], 2023; NCES - National Teacher and Principal Survey [NTPS], 2017; Public School Principal Data Files (Taie et al., 2022); School Superintendents Association [AASA], Tienken, 2020). The purpose of this case study was to explore the Four Frames of an Organization (OD) and the stages of Feminist Theory/Black Feminist Thought (BFT) as it related to the placement of African American administrators in formal leadership positions in a small rural school district in the South (Arinder, 2020; Bolman & Deal, 2021). I engaged in purposeful criterion sampling wherein the participants had completed the foundational credentialing programs and leadership development programs, participated in district-level mentor/mentee programs, and attended local and statewide professional development trainings/conferences. Interviews were collected and analyzed using a three-iteration coding system. I integrated the AI-assisted and In Vivo data sets in the discovery of key findings, themes, and patterns. The key findings are organized by RQs, theories, themes, and patterns. Overall, the participants identified the need for mentorship, formal, and informal support in their career advancement navigation journeys (RQ1). Additionally, perceived race and gender barriers highlighted the issues of disproportionality and underrepresentation of female leaders within the school district (RQ2). Key findings included the identification of ageism and politics as barriers and the participants’ utilization of voice as a strategy or empowerment tool to develop resilience within the school district.
Keywords: Educational leadership; Education and state; Education--Administration; Dissertations, Academic--United States; African American women; School environment; School management and organization; African American school administrators--United States; Teachers--Professional relationships; Sex discrimination in education--United States; Race discrimination in education; Organizational behavior; Rural schools--United States; Educational equalization